2000
DOI: 10.1111/j.1708-8240.2000.tb00202.x
|View full text |Cite
|
Sign up to set email alerts
|

Enamel Microabrasion: A New Approach

Abstract: Enamel microabrasion is a proven method of removing superficial intrinsic enamel discoloration defects. The method is safe, easily performed, and causes no discomfort for the patient. A new commercially available microabrasion system has been introduced by Ultradent Products Inc. In addition, a new tooth isolation material is available, along with a visible light‐activated in‐office hydrogen peroxide solution. This article describes these new products and documents tooth‐color correction for two young patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
21

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 7 publications
2
34
0
21
Order By: Relevance
“…The macroabrasion step which is recomended in the literature before microabrasion 23 was skipped because the presence of enamel is important for treatments such as bleaching and resin infiltration, so even a small thickness of enamel was preserved and kept intact. Also, severely stained and defective structure was located beneath the equator line close to cervical area where the enamel thickness is very low and it is hard to perform a well controled macroabrasion at these areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The macroabrasion step which is recomended in the literature before microabrasion 23 was skipped because the presence of enamel is important for treatments such as bleaching and resin infiltration, so even a small thickness of enamel was preserved and kept intact. Also, severely stained and defective structure was located beneath the equator line close to cervical area where the enamel thickness is very low and it is hard to perform a well controled macroabrasion at these areas.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent to microabrasion, home bleaching was performed to better harmonize tooth color 24 . Bleaching combined with microabrasion was first described by Archambault 25 and since then it has been the recommended treatment approach for dental fluorosis in many publications 12,25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…después de la aplicación del compuesto como: ausencia de sensibilidad térmica postoperatoria en los dientes tratados. 9 Además, el ácido utilizado no es capaz de penetrar la dentina, por lo cual no existe contacto alguno entre la dentina, tejido pulpar y tejido periodontal. 1,10 La expectativa y la ansiedad desarrollada por los padres y del niño en relación con la estética facial del paciente odontopediá-trico, puede comprometer el desenvolvimiento psicológico del niño perjudicando su autoestima.…”
Section: Caso Clínico N°unclassified
“…3 La mezcla de H 3 PO 4 y piedra pómez en una proporción de 1:1, produce acción ácido-abrasiva, ya que provee al diente un aspecto lustroso y brillante permanente, reduciendo las probabilidades de formación de caries en la superficie del mismo. 9,10 Algunos estudios refieren que la acción de ambos ácidos presentan resultados exitosos similares y que el color del esmalte mejora con el tiempo, 15 además…”
Section: Diagnósticounclassified
“…It has been reported that microabrasion could invariably make improvements to the disfigured enamel, but a proportion of the patients were still not satisfied with the change and requested further improvement by composite/porcelain veneers, crowns, or vital bleaching. [11][12][13] Hence, the aims of this study were to investigate which type of opacity could be aesthetically improved by microabrasion to an appearance acceptable to the patient and to explore whether this technique could also be used as an aid to determine the cause of the enamel defect.…”
mentioning
confidence: 99%